Selective RP-HPLC Deternation of Celecoxib in Capsules - Gowri Sankar, D.; Devi Priya, K.; Vamsi Krishna, M.; Latha, P.V.M. (Asian Journal of Chemistry, 2010)
A simple and reproducible reverse phase high performance liquid chromatographic (RPHPLC) method has been developed for the estimation of celecoxib in capsules. The quantification was carried out using a Partisil C-18 octa decyl silane column 250×4.6 mm i.d., 5 μm particle size in isocratic mode, with mobile phase comprising acetonitrile and water in the ratio 60:40 (v/v). The flow rate was 1.0 mL /n and the detection was carried out at 254 nm. The retention time of the drug was 6.35 n and the method produced linear response in the concentration range of 1–40 μg/mL. The proposed method was statistically evaluated and can be applied for routine quality control analysis of celecoxib in capsules.